SARS-CoV-2 immunity and reasons for non-vaccination among healthcare workers from eastern and northern Switzerland: results from a nested multicentre cross-sectional study (Swiss Medical Weekly, 2024)
AIMS OF THE STUDY: We aimed to assess the extent of SARS-CoV-2 humoral immunity elicited by previous infections and/or vaccination among healthcare workers, and to identify reasons why healthcare workers decided against vaccination.METHODS: This nested cross-sectional study included volunteer healthcare workers from 14 healthcare institutions in German-speaking Switzerland. In January 2021, SARS-CoV-2 vaccines were available for healthcare workers. In May and June 2022, participants answered electronic questionnaires regarding baseline characteristics including SARS-CoV-2 vaccination status (with one or more vaccine doses defined as vaccinated) and previous SARS-CoV-2 infections. Unvaccinated participants indicated their reasons for non-vaccination. Participants underwent testing for SARS-CoV-2 anti-spike (anti-S) and anti-nucleocapsid (anti-N) antibodies. Antibody prevalence was described across age groups. In addition, we performed multivariable logistic regression to identify baseline characteristics independently associated with non-vaccination and described reasons for non-vaccination.RESULTS: Among 22,438 eligible employees, 3,436 (15%) participated; the median age was 43.7 years (range 16–73), 2,794 (81.3%) were female, and 1,407 (47.7%) identified as nurses; 3,414 (99.4%) underwent serology testing, among whom 3,383 (99.0%) had detectable anti-S (3,357, 98.3%) antibodies, anti-N (2,396, 70.1%) antibodies, or both (2,370, 69.4%). A total of 296 (8.6%) healthcare workers were unvaccinated, whereas 3,140 (91.4%) were vaccinated. In multivariable analysis, age (adjusted OR [aOR] 1.02 per year, 95% CI 1.01–1.03), being a physician (aOR 3.22, 95% CI 1.75–5.92) or administrator (aOR 1.88, 95% CI 1.27–2.80), and having higher education (aOR 2.23, 95% CI 1.09–4.57) were positively associated with vaccine uptake, whereas working in non-acute care (aOR 0.58, 95% CI 0.34–0.97), active smoking (aOR 0.68, 95% CI 0.51–0.91), and taking prophylactic home remedies against SARS-CoV-2 (aOR 0.42, 95% CI 0.31–0.56) were negatively associated. Important reasons for non-vaccination were a belief that the vaccine might not have long-lasting immunity (267/291, 92.1%) and a preference for gaining naturally acquired instead of vaccine-induced immunity (241/289, 83.4%).CONCLUSIONS: Almost all healthcare workers in our cohort had specific antibodies against SARS-CoV-2 from natural infection and/or from vaccination. Young healthcare workers and those working in non-acute settings were less likely to be vaccinated, whereas physicians and administrative staff showed higher vaccination uptake. Presumed ineffectiveness of the vaccine is an important reason for non-vaccination.